Effectiveness of Self-Generation During Learning is Dependent on Individual Differences in Need for Cognition. - Julia Schindler; Simon Schindler; Marc-André Reinhard (EARLI, 2019)
Self-generated information is better recognized and recalled than read information. This so-called generation effecthas been replicated several times for different types of stimulus material, different generation tasks, and retention intervals. The present study investigated the impact of individual differences in learners' disposition to engage in effortful cognitive activities (need for cognition, NFC) on the effectiveness of self-generation during learning. Learners low in NFC usually avoid getting engaged in cognitively demanding activities. However, if these learners are explicitly instructed to use elaborate learning strategies such as self-generation, they should benefit more from such strategies than learners high in NFC, because self-generation stimulates cognitive processes that learners low in NFC usually tend not to engage in spontaneously. Using a classical word-generation paradigm, we not only replicated the generation effect in free and cued recall but showed that the magnitude of the generation effect increased with decreasing NFC in cued recall. Results are consistent with our assumption that learners higher in NFC engage in elaborate processing even without explicit instruction, whereas learners lower in NFC usually avoid cognitively demanding activities. These learners need cognitively demanding tasks that require them to switch from shallow to elaborate processing to improve learning. We conclude that self-generation is beneficial regardless of the NFC level, but our study extends the existing literature on the generation effect and on NFC by showing that self-generation can be particularly useful for balancing the learning disadvantage of students lower in NFC.